Exciton–phonon coupling and power dependent room temperature photoluminescence of sulphur vacancy doped MoS2via controlled thermal annealing. Issue 36 (9th September 2020) - Mastrippolito, Dario; Palleschi, Stefano; D'Olimpio, Gianluca; Politano, Antonio; Nardone, Michele; Benassi, Paola; Ottaviano, Luca
Abstract : A direct investigation of the exciton–phonon coupling in 2D doped MoS2 by means of power dependent photoluminescence and resonant Raman spectroscopy at room temperature. Abstract : Via experiments performed by varying the doping level of single-layer mechanically exfoliated MoS2 via post exfoliation thermal annealing in the 200–300 °C temperature range, we study the power dependent room temperature (RT) photoluminescence (PL), which is dominated by A type excitons. The PL spectral yields of the as-exfoliated and annealed samples show sub-linear behaviour as a function of the excitation laser power. The PL signal of the 200 °C annealed sample is dominated by the charged exciton (trion) related peak, while the PL signal of the 300 °C annealed sample is dominated by the neutral exciton related peak, and the PL spectral weight of excitons is tunable in this temperature range. The PL signal increase due to annealing and the intensity ratio of the A type excitons are related, showing a hyperbolic tangent trend. We directly quantitatively demonstrate the one-to-one correlation of the RT resonant Raman (632.8 nm) integrated spectral intensity with the corresponding PL spectral yield, providing experimental evidence of the exciton–phonon coupling effect. The in-plane E2g 1 Raman mode exhibits strong coupling with A excitons, while the out-of-plane A1g Raman mode does not. This is an indication of the in-plane spatial symmetry of the A excitons.